JÜRGEN HUBERMAS' SOCIAL CRITICISM OF EDUCATIONAL PRACTICES - Darojat, Jajat; Ilyas, Marfu Muhyidin; Susilawati, Erni; Komariah, Grandson of (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Education is social engineering that is regularly and measurably oriented towards the social changes in society. Therefore, educational practice cannot be separated from the process of social transformation that shapes and prepares individuals to become members of society. In reality, education is like an ivory tower that is alienated from the social reality of society and therefore cannot contribute to social change. This research criticizes educational practices based on Jürgen Hubermas' theory of social criticism, which tends to view education as a conservative-formalistic process. This research uses a descriptive qualitative method with a literary studies approach. The research findings explain that there are two discussions in the study namely; First, the critical theoretical reflection on Jürgen Hubermas's pedagogical practice. That Habermas' communication theory can be understood in educational practice as a process of social transformation. In education, students are positioned as autonomous subjects who have a relationship between educators and students as subjects. Since education is fundamentally a process of constructive individual change, the educational practice paradigm is geared towards intersubjective-emanative relationship patterns. Second, related to the discussion about measuring the role of education in social reconstruction from the perspective of Jürgen Habermas, education is fundamentally a social instrument that plays a role in shaping changes in the social life of society. The role of education cannot be separated from the context of social change, therefore educational practice is part of social engineering regularly aimed at preparing students to become members of society.